Crystal Structure of 4-Hydroxyphenylpyruvate Dioxygenase in Complex with Substrate Reveals a New Starting Point for Herbicide Discovery - Hong-Yan Lin (Research, 2019)
4-Hydroxyphenylpyruvate dioxygenase (HPPD) is a promising target for drug and pesticide discovery. The unknown binding mode of substrate is still a big challenge for the understanding of enzymatic reaction mechanism and novel HPPD inhibitor design. Herein, we determined the first crystal structure of Arabidopsis thaliana HPPD (AtHPPD) in complex with its natural substrate (HPPA) at a resolution of 2.80 Å. Then, combination of hybrid quantum mechanics/molecular mechanics (QM/MM) calculations confirmed that HPPA takes keto rather than enol form inside the HPPD active pocket. Subsequent site-directed mutagenesis and kinetic analysis further showed that residues (Phe424, Asn423, Glu394, Gln307, Asn282, and Ser267) played important roles in substrate binding and catalytic cycle. Structural comparison between HPPA-AtHPPD and holo-AtHPPD revealed that Gln293 underwent a remarkable rotation upon the HPPA binding and formed H-bond network of Ser267-Asn282-Gln307-Gln293, resulting in the transformation of HPPD from an inactive state to active state. Finally, taking the conformation change of Gln293 as a target, we proposed a new strategy of blocking the transformation of HPPD from inactive state to active state to design a novel inhibitor with Ki value of 24.10 nM towards AtHPPD. The inhibitor has entered into industry development as the first selective herbicide used for the weed control in sorghum field. The crystal structure of AtHPPD in complex with the inhibitor (2.40 Å) confirmed the rationality of the design strategy. We believe that the present work provides a new starting point for the understanding of enzymatic reaction mechanism and the design of next generation HPPD inhibitors.